Phylogenetic Investigation of Megapodius cumingii from Kabetan, Central Sulawesi, Based on the RDP1 Gene - Akram; I Made Budiarsa; Yunita Messe (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study investigated the phylogenetic relationships of Megapodius cumingii using bioinformatic analyses. Blood samples were collected from the Kabetan Island population, followed by DNA extraction using the QIAamp DNA Blood Mini Kit, PCR amplification with Takara Ex Taq™ and RDP1.U1/RDP1.L1 primers, and sequencing with BigDye Terminator v3.1 ABI PRISM 3100. Chromatograms were converted into nucleotide sequences using BioEdit, and sequence similarity was assessed using NCBI BLAST. Multiple sequence alignment, model selection, nucleotide composition analysis, and phylogenetic reconstruction were performed in MEGA 12. The RDP1 gene of M. cumingii from Kabetan showed a consistent nucleotide composition with high GC content (55.27%) and high similarity to M. cumingii sequence KF834037.1, with substitutions dominated by transitions (A↔G, T↔C). Maximum likelihood analysis under the T92+G model (1.03) revealed three major clades, with clades 1 and 2 strongly supported (bootstrap = 100). The Kabetan population formed a monophyletic subclade with KF834037.1 (bootstrap = 86) and showed a very short branch length (~0.05 substitutions/site), indicating low intraspecific divergence, with Megapodius tenimberensis as the closest sister taxon. These findings support the utility of RDP1 for phylogenetic resolution within Megapodiidae and provide a preliminary basis for conservation planning and population connectivity assessment of M. cumingii in Wallacea.